Pelatihan IoT Untuk Implementasi Smart Home Di SMKN 8 Padang - Sahid Ridho; Firdaus Firdaus; Yustini Yustini; Zurnawita Zurnawita; Abdi Abdillah; Dedi Tri Laksono (Jurnal Insan Pengabdian Indonesia, 2023)
In the current era of digital connectivity, the Internet of Things (IoT) has gained utmost importance. However, at SMKN 8 Padang, students in Computer Networking and Telecommunications Engineering program lack a comprehensive understanding of IoT and its application in Smart Home systems. To address this, the Community Service Team (PKM) devised an IoT training program with a focus on Smart Home implementation. Through lectures, guidance, and hands-on training, students gained insights into IoT fundamentals, hardware and software components, and practical skills for designing and implementing Smart Home systems. The training sessions proceeded smoothly, and students showed enthusiasm in assembling and connecting devices like Arduino, Relay, and ESP8266. Evaluations revealed that 98.33% of the students improved their knowledge and skills, with 3.33% expressing satisfaction with the training. This IoT training significantly enhanced students' understanding of emerging technologies and motivated them to seek innovative solutions in the future. Empowered with relevant technical skills, SMKN 8 Padang students are expected to contribute to the implementation of Smart Home systems and confidently face the challenges of an increasingly digital and interconnected future